Evaluation of the new respiratory gating system. Issue Volume 1:Issues 4(2017) (21st December 2017) - Shi, Chengyu; Tang, Xiaoli; Chan, Maria
Abstract: Objective: The newly released Respiratory Gating for Scanners (RGSC; Varian Medical Systems, Palo Alto, CA, USA) system has limited existing quality assurance (QA) protocols and pertinent publications. Herein, we report our experiences of the RGSC system acceptance and QA. Methods: The RGSC system integration was tested with peripheral equipment, spatial reproducibility, and dynamic localization accuracy for regular and irregular breathing patterns, respectively. A QUASAR Respiratory Motion Phantom and a mathematical fitting method were used for data acquisition and analysis. Results: The results showed that the RGSC system could accurately measure regular motion periods of 3–10 s. For irregular breathing patterns, differences from the existing Real‐time Position Management (RPM; Varian Medical Systems, Palo Alto, CA) system were observed. For dynamic localization measurements, the RGSC system showed 76% agreement with the programmed test data within ±5% tolerance in terms of fitting period. As s comparison, the RPM system showed 66% agreement within ±5% tolerance, and 65% for the RGSC versus RPM measurements. Conclusions: New functions and positioning accuracy improve the RGSC system's ability to achieve higher dynamic treatment precision. A 4D phantom is helpful for the QA tests. Further investigation is required for the whole RGSC system performance QA.